A Brief Introduction to Tibetan Heroic Epic ‘Gesar’ Studies in China (1931-2016) - D. Bamao (Oriental Studies, 2018)
The article provides a brief introduction to Tibetan heroic epic ‘Gesar’ studies in China (1931-2016). The history of Tibetan heroic epic ‘Gesar’ studies can be traced back to earlier periods. In China, the Tibetan heroic epic ‘Gesar’ was first mentioned by Ren Naiqiang (任乃强, 1894-1989) in May of 1930. The period from 1930 to the late 1970s was devoted to studying the achievements of foreign scientists and the formation of scientific and methodological positions in research the epic ‘Gesar’ by Chinese scientists. During this period, a lot of work was done to collect versions of the epic in different regions of Tibet. From the late 1970s to the mid-1990s, Chinese scholars approved the ‘Gesar’ as an academic discipline in the study of the oral literature of the peoples of China. Since the 1990s until now work has been conducted on in-depth study of the epic and the formation of ‘Gesar’ studies as an independent scientific direction.